Importancia de residuos básicos de la proteína ChrA de Pseudomonas aeruginosa - Moreno Contreras, María Guadalupe (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
The CHRA Pseudomonas aeruginosa protein confers resistance to chromate and belongs to the family of transporters CHR, which consists of 135 homologous proteins. By random mutagenesis and site-directed they have identified several essential amino acids for protein function, and because the hydrophobic character of these amino acids, have been assigned a structural role. The resistance mechanism is CHRA chromate expulsion oxyanion cytoplasm, so it is possible that the basic amino acids, positively charged arginine (Arg) and lysine (Lys), interact with the chromate for binding and ejection. The aim of this study was to evaluate the role of conserved basic amino acids in the function of CHRA. For this eight residues were analyzed: Lys-37 and Arg-34, located in the transmembrane segment (STM) I; Lys-248, located in the STM VIII; Arg-55, Arg-98, Arg-201 and Lys-394 and Arg-in Absorbent 154 handles the interface STM IV and cytoplasm. Using directed mutagenesis mutants they were obtained at selected amino acids to which the level of resistance was evaluated regarding chromate wild protein in susceptibility testing in nutrient broth at 37 ° C. The Lys-37 (Arg, Thr and Leu), Arg-34 (Thr), Arg-55 (Thr), Arg-98 (Lys), Arg-201 (Lys), Lys2-48 (Arg) and Lys mutants 394 (Arg) had a 75-100% resistance compared to the wild-type protein. Arg-55 mutant (Leu and Lys), Arg-154 (Lys) and Lys-394 (Thr and Leu) had 45-60% of resistance. The most affected mutants were Lys37- (Glu), Arg-154 (Leu) and Arg201 (Thr and Leu) with 14-30% resistance, and Lys-248 (Thr and Leu) which acted as the sensitive control.

La proteína ChrA de Pseudomonas aeruginosa confiere resistencia a cromato y pertenece a la familia de transportadores CHR, la cual consta de 135 proteínas homologas. Mediante mutagenesis al azar y sitio-dirigida se han identificado varios aminoácidos esenciales para la función de la proteína, y debido el carácter hidrofóbico de dichos aminoácidos, se les ha asignado un papel estructural. El mecanismo de resistencia de ChrA consiste en la expulsión del oxianion cromato del citoplasma, por lo que es posible que los aminoácidos básicos, cargados positivamente, arginina (Arg) y lisina (Lys), interaccionen con el cromato para su unión y expulsión. El objetivo de este trabajo fue evaluar el papel de aminoácidos básicos conservados en la función de ChrA. Para ello se analizaron ocho residuos: Lys-37 y Arg-34, ubicadas en el segmento transmembranal (STM) I; Lys-248, ubicada en el STM VIII; Arg-55, Arg-98, Arg-201 y Lys-394 en asas hidrofilicas y Arg-154 en la interface del STM IV y el citoplasma. Utilizando mutagenesis dirigida se obtuvieron mutantes en los aminoácidos seleccionados, a las cuales se evaluó su nivel de resistencia a cromato con respecto a la proteína silvestre en pruebas de susceptibilidad en caldo nutritivo a 37°C. Las mutantes Lys-37(Arg, Thr y Leu), Arg-34(Thr), Arg-55(Thr), Arg-98(Lys), Arg-201(Lys), Lys2-48(Arg) y Lys- 394(Arg) presentaron un 75-100% de resistencia respecto a la proteína silvestre. Las mutantes Arg-55(Lys y Leu), Arg-154(Lys) y Lys-394(Thr y Leu) presentaron un 45-60% de resistencia. Las mutantes más afectadas fueron Lys37-(Glu), Arg-154(Leu) y Arg201 (Thr y Leu) con un 14-30% de resistencia, y Lys-248(Thr y Leu) las cuales se comportaron como el control sensible.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2006-0009; Proteína; Aminoácidos; Arginina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3823